Logistics activity in the regional market of tourist services - Alkema, Viktor; Алькема, Віктор Григорович (Scientific Center of Innovative Research, 2022)
This article forms modern theoretical and methodological principles on the nature, place and role of logistics in the field of regional tourism. The influenceof the content and quality of logistics activities on the effectiveness and efficiency of tourist services is determined. Modern destructive factors influencing the development of both regional and international tourism have been identified. It is proved that logistics activity helps to strengthen the competitive position of the subjects of the market of tourist services in the regional tourist market. The content of the article reveals a set of basic terms for the interpretation of the definition of "logistics activities" and the main approaches to understanding it. The study of the role and place of logistics activities was carried out within the system-activity approach. The genesis of various aspects of logistics activity on the basis of the analysis ofworks of domestic and foreign scientists is considered. The generalized purpose of logistics activity is formalized and its tasks within the limits of exogenous and endogenous approaches are defined. Peculiarities of logistics activity in the regional tourism market are considered.The author's vision of the institutional structure of the subjects of the market of tourist services in Ukraine is formed and the place and role of the subjects of logistic activity in this market are determined. The logistic analysis of the subjects of the regional tourism market is carried out. The basic object of management in logistics, namely the logistics flow, is defined as the basic sign of differentiation of these subjects. The tendencies of development of the subjects of the regional tourism market are forecasted and the algorithm of their transformation into the subjects of logistic activity is offered. The process-functional structuring of the logistics activity of the subjects of regional tourism has been carried out.The basic postulates concerning logistics activity in the market of tourist services are formulated.A systematic decomposition of the components of logistics activity is presented. The place of logistic activity in the management system of the organization is determined. The nature of the influence of the organizational mechanism of logistics management on the effectiveness and efficiency of the regional tourism market is established. The directions of managerial activity of managers of logistics companies are revealed. The main types of logistics activities in the field of tourism are presented
Keywords: tourism; regional tourism market; tourist services; tourist flow; logistics activity; subjects of logistics activity; efficiency; effectiveness; social responsibility